2021
DOI: 10.1101/2021.02.10.21251460
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge and practices related to menstruation among Lucknow college students in North India: results from a cross-sectional survey

Abstract: Background: Girls in many low and middle-income countries enter puberty with knowledge gaps and misconceptions about menstruation may lead to unsafe hygienic practices that increase health risk. Despite such importance, educated girls' knowledge and hygienic practice towards menstruation are not well addressed in India. Consequently, the present study attempted to assess menstrual hygiene knowledge and practice among college students in Lucknow city in north India. Method: An online college-based cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…We found that nearly all of our study participants reported knowledge improvements in areas such as the menstrual cycle (89.0%) and pregnancy health (84.6%). This is of particular relevance given the low level of health literacy among adolescents and women about their reproductive health as reported in multiple studies [15,16,19,21,54]. These results are also in line with a study independently conducted by Karasneh at el.…”
Section: Knowledge and Health Improvements Among Flo App Userssupporting
confidence: 88%
See 2 more Smart Citations
“…We found that nearly all of our study participants reported knowledge improvements in areas such as the menstrual cycle (89.0%) and pregnancy health (84.6%). This is of particular relevance given the low level of health literacy among adolescents and women about their reproductive health as reported in multiple studies [15,16,19,21,54]. These results are also in line with a study independently conducted by Karasneh at el.…”
Section: Knowledge and Health Improvements Among Flo App Userssupporting
confidence: 88%
“…There is a big knowledge gap among adolescent girls and adult women, especially in low and middle income countries, about menstrual cycle health [15,16], fertility [15,17], healthy pregnancy [18] and overall women's health and wellbeing [19][20][21]. A North Indian study has found that only 31% of respondents reported the right definition of the menstrual cycle [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Absar Ahmad et al . [ 12 ], in their study on knowledge and practices associated with menstruation among Lucknow college students in north India in 2020, found that students whose fathers were graduates had significantly lower knowledge of menstruation than students whose fathers were school-educated (AOR 0.634, 95% CI: 0.426–0.944). Similarly, students whose fathers’ occupations were “Other” had lower knowledge of menstruation than students whose fathers were farmers (AOR 0.671, 95% CI: 0.466–0.967).…”
Section: Discussionmentioning
confidence: 99%
“…Absar Ahmad et al . [ 12 ], in their study in Lucknow, North India in 2020, found that religion, mother occupation, and family type were associated with good hygiene practice of menstruation among students. Students of other religions (Sikhism and Christianity) were 88% less likely to had good menstrual hygiene practices than Hindu students (AOR = 0.11, 95% CI: 0.048–0.273).…”
Section: Discussionmentioning
confidence: 99%